Teeny tiny woman (The) - O'Connor, Jane (New York : Random House, 1986)
A teeny tiny woman who puts a teeny tiny bone she finds in a churchyard away in a cupboard before she goes to sleep is awakened by voice demanding the return of the bone.
Keywords: Ghosts-Folklore; Folklore-England